Cbf1p modulates chromatin structure, transcription and repair at the Saccharomyces cerevisiae MET16 locus. - Ferreiro, J; Powell, N; Karabetsou, N; Kent, N; Mellor, J; Waters, R (2004)
The presence of damage in the transcribed strand (TS) of active genes and its position in relation to nucleosomes influence nucleotide excision repair (NER) efficiency. We examined chromatin structure, transcription and repair at the MET16 gene of wild-type and cbf1Delta Saccharomyces cerevisiae cells under repressing or derepressing conditions. Cbf1p is a sequence-specific DNA binding protein required for MET16 chromatin remodelling. Irrespective of the level of transcription, repair at the MspI restriction fragment of MET16 exhibits periodicity in line with nucleosome positions in both strands of the regulatory region and the non-transcribed strand of the coding region. However, repair in the coding region of the TS is always faster, but exhibits periodicity only when MET16 is repressed. In general, absence of Cbf1p decreased repair in the sequences examined, although the effects were more dramatic in the Cbf1p remodelled area, with repair being reduced to the lowest levels within the nucleosome cores of this region. Our results indicate that repair at the promoter and coding regions of this lowly transcribed gene are dependent on both chromatin structure and the level of transcription. The data are discussed in light of current models relating NER and chromatin structure.